Kairomone-induced changes in foraging activity of the larval ectoparasitoid Holepyris sylvanidis are linked with an increased number of male parasitoid offspring - Awater-Salendo, Sarah; Hilker, Monika; Fürstenau, Benjamin (Frontiers in Ecology and Evolution, 2023)
Interactions between stored product pest insects and their parasitoids are well known to be mediated by infochemicals. However, little knowledge is available about the extent to which parasitoid responses to host kairomones improve host search and parasitization success. Here, we tested whether the release of host-specific kairomones of the confused flour beetle, Tribolium confusum, improves host finding of the larval ectoparasitoid Holepyris sylvanidis. Previous studies revealed that volatiles from host larval feces [i.e., (E)-2-nonenal and 1-pentadecene] attract the parasitoid. To determine the most attractive concentration of these two key components, we conduced Y-tube olfactometer bioassays. Most female parasitoids were attracted to a mixture of (E)-2-nonenal and 1-pentadecene at the lowest concentration, while the highest concentration was repellent. Volatiles from host adults (methyl-p-benzoquinone and 4,8-dimethyldecanal) did not attract the parasitoid females at any of the concentrations tested. In flight cage experiments, we analyzed the host finding success of H. sylvanidis by offering host larvae in a Petri dish for 3 days (i) with additionally applied host larval kairomones in the most attractive concentration (test) or (ii) without additional kairomones (control). In test cages, the parasitoids removed a significantly higher number of paralyzed host larvae from the initial population within 48 h than in control cages. After 72 h, significantly more host larvae were parasitized in test cages than in the control. The offspring of parasitoids in test cages differed from the one in control cages by total numbers and especially the number of males. Significantly more parasitoids emerged from the parasitized host larvae in test cages, with enhanced male offspring. Our study demonstrates that the parasitoid’s response to host-associated volatiles can improve parasitization success but also affects the number of males in the parasitoids’ progeny.